(untitled) (Journal of the College of Education for Women, 2020)
Domestic violence, or as sometimes known as family abuse, is usually related to a domestic or local setting as in cohabitation or in marriage. It can take the forms of being physical, verbal, economic or emotional. Globally, most of the domestic violence is overwhelmingly directed to females as they tend to experience and receive severe forms of violence, most likely because they do not involve their intimate, or sometimes even non-intimate partners, in the process of mental and physical self-defense. Sometimes countries justify domestic violence directed to females, they may be legally permitted when the reasons behind it are related to issues of women’s infidelity. Usually, the permission to violent acts is related to the level of gender equality postulated in these countries. Familial or domestic violence may progress when it is directed against any partner in society. In its evolution, domestic violence may develop different violent dynamics out of human choices. In Glaspell’s play, domestic violence has led the hard-natured Mr. Wright to his death, a nature that is articulated to his wife as a fatal execution of her own freedom and humanity. The kitchen, a place which men consider trivial, holds the clues leading the female characters in the play to discover the identity of the murderer. This discovery causes, in the audience as well as in the female characters, a dilemma of judging the domestic violence executed by the murderer under the pressures of emasculated patriarchal culture overwhelming that closed society.